IITA contributes to our effectiveness - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2011)
Mrs. Olufunke Awosusi is the Plant Quarantine Officer with the Nigerian Agricultural Quarantine Service (NAQS) in the Federal Ministry of Agriculture. Charged with the responsibility of protecting the Nigerian agricultural economy from the ruins of pests, Awosusi in this interview speaks on the role of the NAQS and the collaboration with IITA.